2016
DOI: 10.1002/jbm.a.35747
|View full text |Cite
|
Sign up to set email alerts
|

In situ supramolecular hydrogel based on hyaluronic acid and dextran derivatives as cell scaffold

Abstract: In this study, hyaluronic acid-β-cyclodextrin conjugate (HA-CD) and dextran-2-naphthylacetic acid conjugate (Dex-NAA) were synthesized as two gelators. The degrees of substitution (DS) of these two gelators were determined to be 15.5 and 7.4%, respectively. Taking advantages of the strong and selective host-guest interaction between β-CD and 2-NAA, the mixture of two gelators could form supramolecular hydrogel in situ. Moreover, the pore size, gelation time, swelling ratio as well as modulus of the hydrogel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…The gelation time was determined by the vial tilting method. 28 The experiments were repeated for three times.…”
Section: Synthesis Of Polyethyleneglycol Diacrylatementioning
confidence: 99%
“…The gelation time was determined by the vial tilting method. 28 The experiments were repeated for three times.…”
Section: Synthesis Of Polyethyleneglycol Diacrylatementioning
confidence: 99%
“…Recent studies have suggested that some types of cells cultured on two-dimensional substrates do not recapitulate the phenotype of the cells in vivo [86,87]. To date, gelatin-based materials, such as Matrigel, have been used as three-dimensional cell culture materials, and other three-dimensional culture materials based on hydrogels are currently being developed [88].…”
Section: Chemical Modulation Of Hydrogels Crosslinked By Noncovalent mentioning
confidence: 99%
“…In our body, fibrous extracellular matrix proteins, such as collagen, often exhibit a highly anisotropic topography that dictates the morphology, directional order, and migration of cells, called contact guidance [89][90][91][92]. As nanofibers of proteins, such as collagen and gelatin, have been utilized for various applications, including wound healing and tissue engineering [88,93,94], protein nanofibers with stimuli-responsive functional groups seem to be a promising and biologically relevant target. Moreover, fabrication of stimuli-responsive, three-dimensional microstructures comparable to or smaller than the size of cells with advanced three-dimensional printing technology is a promising strategy to microfabricate cellular scaffolds with a defined geometry [95].…”
Section: Chemical Modulation Of Hydrogels Crosslinked By Noncovalent mentioning
confidence: 99%
“…A supramolecular hydrogel using HA and dextran derivatives with molecular recognition was developed as a strategy to improve HA retention and mechanical properties. Chen et al [204] modified HA with β-cyclodextrin and dextran with 2-naphtylacetic acid to produce host-guest hydrogels. By varying the number of inclusion complexes, through the amount of modified dextran in the formulations, the authors observed a decrease in pore size and swelling ratio, as well as an increase in G' with increasing dextran content [204].…”
Section: Dextranmentioning
confidence: 99%
“…Chen et al [204] modified HA with β-cyclodextrin and dextran with 2-naphtylacetic acid to produce host-guest hydrogels. By varying the number of inclusion complexes, through the amount of modified dextran in the formulations, the authors observed a decrease in pore size and swelling ratio, as well as an increase in G' with increasing dextran content [204]. Additionally, the developed system was able to sustain high viability rates of entrapped cells [204].…”
Section: Dextranmentioning
confidence: 99%